Practical Guidelines for Effective Bank Resolution - Bolzico, Javier (World Bank, Washington, DC, 2012)
This study adopts a practical approach in developing a set of guidelines on designing a bank resolution framework and implementing efficient bank resolution methods in Latin America. It identifies six pillars that are useful for establishing a bank resolution framework. The study aims to guide policymakers choose from a set of bank resolution methods, by outlining their advantages and disadvantages and establishing efficiency requirements. The focus is on the good-bank/bad-bank approach, which is a type of purchase and assumption mechanism that has increasingly become part of the newer legal frameworks in Latin America. The good-bank/bad-bank approach is an effective bank resolution method because it can be very successful in meeting certain efficiency criteria, including the minimization of contagion costs and preservation of business.